Phenotype, Function, and Mobilization of 6-Sulfo LacNAc-Expressing Monocytes in Atopic Dermatitis - Baran, Wojciech; Oehrl, Stephanie; Ahmad, Fareed; Döbel, Thomas; Alt, Christina; Buske-Kirschbaum, Angelika; Schmitz, Marc; Schäkel, Knut (Frontiers in Immunology, 2018)
Mononuclear phagocytes (MPs) are important immune regulatory cells in atopic dermatitis (AD). We previously identified 6-sulfo LacNAc-expressing monocytes (slanMo) as TNF-α- and IL-23-producing cells in psoriatic skin lesions and as inducers of IFN-γ-, IL-17- and IL-22-producing T cells. These cytokines are also upregulated in AD and normalize with treatment, as recently shown for dupilumab-treated patients. We here asked for the role of slanMo in AD. Increased numbers of slanMo were found in AD skin lesions. In difference to other MPs in AD, slanMo lacked expression of FcɛRI, CD1a, CD14 and CD163. slanMo from blood of patients with AD expressed increased levels of CD86 and produced IL-12 and TNF-α at higher amounts than CD14+ monocytes and myeloid dendritic cells. While CD14+ monocytes from patients with AD revealed a reduced IL-12 production, we observed no difference in the cytokine production comparing slanMo in AD and healthy controls. Interestingly, experimentally induced mental stress, a common trigger of flares in patients with AD, rapidly mobilized slanMo which retained their high TNF-α-producing capacity. This study identifies slanMo as a distinct population of inflammatory cells in skin lesions and as proinflammatory blood cells in patients with AD. slanMo may therefore represent a potent future target for treatment of AD.